Distributed Computing and Internet Technology 12th International Conference, ICDCIT 2016, Bhubaneswar, India, January 15-18, 2016, Proceedings - Bjorner, Nikolaj; Prasad, Sanjiva; Parida, Laxmi (Information Systems and Applications, incl. Internet/Web, and HCI, 2016)
This book constitutes the proceedings of the 12th International Conference on Distributed Computing and Internet Technology, ICDCIT 2016, held in Bhubaneswar, India, in January 2016. The 6 full papers, 7 short papers and 11 poster papers presented in this volume were carefully reviewed and selected from 129 submissions. The ICDCIT conference focusses on distributed computing, internet technologies, and societal applications. The book also contains 3 full paper invited talks. .